From curriculum design to enactment in technology enhanced mathematics instruction—Mind the gap!. (2019) - Clark-Wilson, Alison; Hoyles, Celia
Highlights: Lesson enactments reveal maths teachers' knowledge for teaching with technology. Develops a framework for maths teachers' knowledge for teaching with technology. Offers a methodology to evaluate lesson plans for teaching maths with technology. Case study data highlights that gap between planned and real lesson enactments. Abstract: A 3-year study of 209 mathematics teachers in England implementing Cornerstone Maths curriculum units for lower secondary mathematics that embed dynamic technology provides a rich data set on teachers' curriculum enactments. Focusing on the curriculum unit on linear functions, we report gaps between teachers' planned and actual curriculum enactments, which are to be expected. By focusing on the 'at scale' and individual teacher outcomes, the research reveals new insights into the complexities of technology integration in mathematics instruction. For example, the case of Amy serves to highlight how a teacher's intended enactment is challenging in reality, whilst providing worthwhile classroom experience that supported the emergence of professional knowledge for teaching mathematics with technology.